Long-run trends in the U.S. SES-achievement gap - Hanushek, Eric Alan,Peterson, Paul E.,Talpey, Laura M.,Woessmann, Ludger (CESifo, Center for Economic Studies & Ifo Institute, 2020)
Rising inequality in the United States has raised concerns about potentially widening gaps in educational achievement by socio-economic status (SES). Using assessments from LTT-NAEP, Main-NAEP, TIMSS, and PISA that are psychometrically linked over time, we trace trends in achievement for U.S. student cohorts born between 1954 and 2001. Achievement gaps between the top and bottom quartiles of the SES distribution have been large and remarkably constant for a near half century. These unwavering gaps have not been offset by improved achievement levels, which have risen at age 14 but have remained unchanged at age 17 for the past quarter century.
10419/216507
Keywords: Graue Literatur; student achievement; inequality; socio-economic status; United States; NAEP; TIMSS; PISA